2010
DOI: 10.1262/jrd.09-214h
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Glutathione and .BETA.-Mercaptoethanol Treatment During In Vitro Maturation of Porcine Oocytes on Early Embryonic Development in a Culture System Supplemented with L-cysteine

Abstract: Abstract. Various methods have been used to remove reactive oxygen species (ROS) generated from in vitro culture (IVC) conditions that can cause cell injury or death, including the application of low oxygen (O2) tension and the addition of antioxidants. The beneficial effects of antioxidants and O2 tension on IVC of porcine embryos, however, are controversial among researchers. In this study, we sought to determine the effects and optimal concentrations of antioxidants for the development of porcine embryos in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 45 publications
(59 reference statements)
2
35
2
2
Order By: Relevance
“…Our results agree with this study, as we found supplementation of melatonin to decrease the ROS produced during maturation. The level of melatonin appears to impact the success of oocyte maturation, as a previous study reported minimal improvements, however the levels were lower than those used in the current study (Choe et al, 2010). Shi et al (2009) reported that the concentrations of melatonin change as the follicle changes size, suggesting an effect of melatonin in oocyte maturation: as the follicle size increased, the levels of melatonin decreased.…”
Section: Discussioncontrasting
confidence: 43%
“…Our results agree with this study, as we found supplementation of melatonin to decrease the ROS produced during maturation. The level of melatonin appears to impact the success of oocyte maturation, as a previous study reported minimal improvements, however the levels were lower than those used in the current study (Choe et al, 2010). Shi et al (2009) reported that the concentrations of melatonin change as the follicle changes size, suggesting an effect of melatonin in oocyte maturation: as the follicle size increased, the levels of melatonin decreased.…”
Section: Discussioncontrasting
confidence: 43%
“…Orn is an intermediary in the synthesis of polyamines, derived from the conversion of Arg to Orn by arginase followed by conversion of Orn to polyamines by ornithine decarboxlyase (ODC1), which is essential for embryogenesis and placental development (Fozard et al 1980;Bazer et al 2012). Cys, a member of the functional amino acids (defined as regulators of key metabolic pathways benefiting survival, growth, development, reproduction and health; Wu et al 2009), has been shown to improve the development of porcine blastocysts in vitro (Choe et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several IVM approaches have been applied, such as oocyte co-culture with follicular cells (Zheng and Sirard 1992;Ding and Foxcroft 1994;Agung et al 2010), or supplement addition to the IVM defined media with: porcine follicular fluid (Naito et al 1988;Yoshida et al 1992;Ka et al 1997), follicular fluid meiosis-activating sterol (Faerge et al 2006), bovine serum albumin (Zheng and Sirard 1992), fetal bovine serum (Kishida et al 2004), fetal calf serum (Naito et al 1988), epidermal growth factor (EGF) (Ding and Foxcroft 1994;Uhm et al 2010), β-mercaptoethanol (Abeydeera et al 1998), cysteine (CYS) (Yamauchi and Nagai 1999;Yoshioka et al 2003;Kobayashi et al 2007;Choe et al 2010), ascorbic acid (Tatemoto et al 2001), leptin (Craig et al 2005;Jin et al 2009) or lycopene (Watanabe et al 2010), among others.…”
Section: Introductionmentioning
confidence: 99%